Do diabetes and obesity affect the metabolic response to exercise?. Issue 4 (July 2017) - Plomgaard, Peter; Weigert, Cora
Abstract : Purpose of review: Exercise is recommended as therapeutic intervention for people at risk to develop type 2 diabetes to prevent or treat the disease. Recent studies on the influence of obesity and type 2 diabetes on the outcome of exercise programs are discussed. Recent findings: Poor glycemic control before an intervention can be a risk factor of reduced therapeutic benefit from exercise. But the acute metabolic response to exercise and the transcriptional profile of the working muscle is similar in healthy controls and type 2 diabetic patients, including but not limited to intact activation of skeletal muscle AMP-activated kinase signaling, glucose uptake and expression of peroxisome proliferator-activated receptor gamma coactivator 1α. The increase in plasma acylcarnitines during exercise is not influenced by type 2 diabetes or obesity. The hepatic response to exercise is dependent on the glucagon/insulin ratio and the exercise-induced increase in hepatokines such as fibroblast growth factor 21 and follistatin is impaired in type 2 diabetes and obesity, but consequences for the benefit from exercise are unknown yet. Summary: Severe metabolic dysregulation can reduce the benefit from exercise, but the intact response of key metabolic regulators in exercising skeletal muscle of diabetic patients demonstrates the effectiveness of exercise programs to treat the disease.